2018
DOI: 10.5937/gads53-17713
|View full text |Cite
|
Sign up to set email alerts
|

Transversal analysis of scoliotic disorders at young adolescents from urban and rural areas

Abstract: The main aim of the research is to determine the frequency, severity, structure, and possible differences of spinal disorders among the girls from urban and rural areas in Montenegro. Research of transversal character included 155 female respondents, 77 of whom were from urban and 78 from rural areas, the average age 13.7 years. The analysis of scoliotic disorders was performed by using several combined techniques and methods of measurement: somatoscopy method, method by using plumb line and ruler, test of rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
1
0
2
Order By: Relevance
“…on the other hand, the results of the present study do not agree with those obtained by Čanjak et al [22], who stated that all types of scoliosis were fairly distributed among girls of different socio-economic status. This may be attributed to gender differences, as we conducted our study in male students only.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…on the other hand, the results of the present study do not agree with those obtained by Čanjak et al [22], who stated that all types of scoliosis were fairly distributed among girls of different socio-economic status. This may be attributed to gender differences, as we conducted our study in male students only.…”
Section: Discussioncontrasting
confidence: 99%
“…This leads to the conclusion that living in the countryside does not necessarily mean living a healthy life in all ways, but it also has some flaws, and that the number of factors causing spinal deformities is much greater in urban than in countryside areas. This contrasts with the observations reported by Čanjak et al [22], who found no significant difference in the prevalence of scoliosis between girls in urban and in rural areas.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation